Interdisciplinary and Project-Based Service Learning for Smart and Connected Communities: Insights from ENDEAVR - Li, Wei; Bian, Jiahe; Lee, Chanam; Bologan, Anatol; Chaspari, Theodora; Calvesbert, Tyrene; Masterson, Jaimie; Stillisano, Jacqueline; Wright, Kim; Shields, Samantha; Fowler, Debra (Journal of Interdisciplinary Studies in Education, 2023)
The demands are increasing for higher education institutions to implement pedagogies engaging students with emerging technologies to address real-world challenges. Innovative approaches are needed to provide students with hands-on, project-based learning experience in interdisciplinary settings. To meet these demands, specifically related to smart and connected communities, a team of educators created an interdisciplinary and project-based service-learning program named Envisioning the Neo-traditional Development by Embracing the Autonomous Vehicles Realm (ENDEAVR) in collaboration with community and industry partners. The ENDEAVR team piloted the program during the 2019-2020 academic year. Program evaluation was conducted using both pre-post surveys and focus groups centered on the program’s impact on students’ critical thinking and problem-solving skills. Based on the analysis and reflections from the pilot implementation, this article identifies key lessons learned in terms of teaching, learning, and institutional management.